REVIEW OF METHODS AND MEANS OF MONITORING THE AIR POLLUTION - Isaenko, Volodymyr; Zaporozhets, Artur; Babikova, Katerina; Gulevets, Dmytro; Savchenko, Serhii (Proceedings of National Aviation University, 2019)
The article analyzes the current state of methods and means of monitoring air pollution in Ukraine. The issues of the formation of pollutants during the combustion of various types of fuel (gaseous, liquid, solid) in large power plants are considered. The data about the largest sources of air pollution in Ukraine are given. The main disadvantages of the model of the spread of pollutants in the air, which is used as a base, are reflected. The current state of air pollution monitoring systems, both in Ukraine and in other countries, is investigated. The improvement of the existing air pollution monitoring system based on unmanned aerial vehicles is proposed.